2008
DOI: 10.1002/cyto.a.20635
|View full text |Cite
|
Sign up to set email alerts
|

Microinjected antibodies interfere with protein nucleocytoplasmic shuttling by distinct molecular mechanisms

Abstract: The observation that some antibodies can enter the nucleus after their microinjection into the cytoplasm established the principle of protein nucleocytoplasmic shuttling. Here, we introduce the concept of stationary antibodies for studying nuclear transport, particularly of native proteins. Contrary to the aforementioned translocating immunoglobulins, stationary antibodies do not cross the nuclear envelope. They are distinguished by their ability to trigger the nucleocytoplasmic redistribution of their antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
2
1
0
Order By: Relevance
“…S1 ). These findings are in agreement with previous observations obtained after microinjection of the 3E9 antibody, which binds to native β-importin 14 . Since HeLa cells do not contain HPV E6 protein, the 4C6 mAb remained in the cytoplasmic compartment, as expected.…”
supporting
confidence: 93%
“…S1 ). These findings are in agreement with previous observations obtained after microinjection of the 3E9 antibody, which binds to native β-importin 14 . Since HeLa cells do not contain HPV E6 protein, the 4C6 mAb remained in the cytoplasmic compartment, as expected.…”
supporting
confidence: 93%
“…1A and B, gray-and-white panels). This is in agreement with a previous study showing that Imp ␤ antibodies preclude the formation of carrier᎑cargo complexes by preventing Imp ␤ and Imp ␣ interactions and subsequent reexport from the nuclear basket (62).…”
Section: Resultssupporting
confidence: 94%
“…This finding has not previously been reported. However, intracellular trafficking of other proteins is well known to occur in neurons [ 33 - 36 ], and studies of molecules injected into non-neuronal cell types have demonstrated similar intracellular trafficking of proteins - including injected antibodies - from cytoplasm into cell nuclei [ 37 - 40 ].…”
Section: Discussionmentioning
confidence: 99%